Employment and budgeting decisions of low-income working families over a period of welfare reform - Wiggan, Jay (2005)
This study examines the implicit assumptions underpinning reforms to the tax and benefit system by the Labour Governments since 1997. It questions whether individuals are income-maximising individuals responsive to changes in the costs and benefits associated with employment. The Working Families' Tax Credit and its replacements the Working Tax Credit and Child Tax Credit, elements of the Government's strategy for encouraging employment and reducing child poverty (HM Treasury, 2001), contain an unspoken acceptance of a particular 'rational economic man' model of behaviour. Recent sociological research around employment and parenting indicates that decision-making is more nuanced than the rational economic model allows. Duncan and Edwards (1999) suggest instead a 'gendered moral rationalities' model, placing specific socially negotiated moral understandings of children's needs at the centre of employment decisions, with financial incentives, a secondary concern. A central question of this thesis is therefore, do prior policy assumptions about employment and budgeting decisions accord with reality? How has the reform of the tax and benefit system affected decision-making around employment and family budgeting, and what has it meant for individuals and their families?